Development of a new hexaploid spring wheat (Triticum aestivum L.) variety “NIFA NIJAT-23” for commercial cultivation in irrigated areas of Khyber Pakhtunkhwa - Syed Tariq Shah; Muhammad Irfaq Khan (International Journal of Applied and Experimental Biology)
Sustainable wheat farming requires an ongoing process of variety development, release, and quality seed production of new high yielding and disease resistant varieties. Farmers in Khyber Pakhtunkhwa are currently cultivating several wheat cultivars, including NIFA AMAN-17, NIFA AWAZ-19, PIRSABAK-21, ZARGHUN-21, PIRSABAK-19, GULZAR-19, KHAISTA-17, PIRSABAK-15, INSAF-15, KP-15 and LALMA-13 under both irrigated and rainfed circumstances. The frequent changes in disease virulence, particularly yellow rust and leaf rust observed frequently over the last three years in KP, have forced breeders to develop new resistant varieties in order to increase productivity. The new hexaploid spring wheat variety NIFA NIJAT-23 (CTHN-162056) developed at NIFA has demonstrated resistance to yellow rust during testing in the Khyber Pakhtunkhwa Wheat Yield Trials (KPWYT) at 13 distinct locations in 2019-20, and this variety with a grain yield of 3337 kg ha-1 has been placed at the third position among 24 test entries. Under normal planting conditions in 2020-21, the NUWYT (National Uniform Wheat Yield Trial) pooled analysis revealed that CTHN-162056 secured the 1st position and provided the greatest mean grain yield of 4701 kg ha-1 across all the candidate lines throughout Pakistan at 31 locations. According to the data reported by the Crop Diseases Research Institute (CDRI), Department of Plant and Environmental Protection, National Agricultural Research Centre (NARC), Islamabad, it has demonstrated highly desirable relative resistance index (RRI) for two consecutive years (2020-21 & 2021-22). The Provincial Seed Council (PSC), Khyber Pakhtunkhwa approved CTHN-162056 and registered as a potential variety “NIFA NIJAT-23”.